Dari Bid’ah ke Beradaptasi: Studi Pergeseran Praktik Keagamaan Warga Muhammadiyah di Aceh Barat Daya - Nuzula, Wiwin; Nirzalin, Nirzalin; Nurdin, Abidin (Jurnal Community, 2025)
Muhammadiyah is present in Indonesia based on the doctrine of anti-Superstition, Bid'ah and Churafat (TBC). One aspect of Muhammadiyah's rejection is the practice of local Islamic cultural traditions in Southwest Aceh in the form of the implementation of the Maulod, Kenduri Blang and Kenduri Jeurat which are considered heretical. However, the actual reality shows that muhammadiyah followers, especially in Kuala Batee District, Southwest Aceh, are starting to get involved in the practice of local Islamic tradition rituals. This reality is the main impetus for this article to answer the question of why the followers of the muhammadiyah Association changed their religious practices from being anti-local Islamic cultural practices which are considered heretical to accepting and even getting involved in the procession. This research was conducted qualitatively with the main support of data collection carried out through participant observation, in-depth interviews, In order to be stronger and more authoritative, the use of relevant documents as secondary data was also used. This article found that the shift in religious practices of Muhammadiyah followers in Aceh Barat Daya is done to strengthen social existence so that they can interact safely and comfortably in the local community  that adheres to dominant Islamic traditions.